Research progress on pathophysiologic mechanisms, clinical treatment and predictive biomarkers in bronchopulmonary dysplasia: from the perspective of oxidative stress - Li, Min; Cheng, Wen-Xiang; Li, Shuo; Wang, Jing; Chen, Yan-Rui; Li, Liang; Yang, Gui (Frontiers in Pediatrics, 2025)
With the global rise in preterm birth rates, bronchopulmonary dysplasia (BPD) continues to be a significant problem, affecting morbidity and mortality in surviving preterm infants. Preterm infants are particularly susceptible to oxidative stress induced by sudden increases in oxygen concentration, which plays a crucial role in the pathogenesis of BPD. Herein, we addressed the pathophysiologic mechanisms, clinical treatment, and predictive biomarkers of BPD from an oxidative stress perspective. We first review the importance of oxygen in preterm infants and point out that sustained exposure to hyperoxia exacerbates the susceptibility of the immature lung to free radicals. The antioxidant properties of clinical therapies for BPD in preterm infants are then summarized. Subsequently, based on lipid, protein, and DNA damage mechanisms, we obtained the most comprehensive, accurate, and representative oxidative stress biomarkers. A total of 37 research papers on oxidative stress in BPD were collected. We conclude that 8-OHdG is the most promising biomarker for early prediction of BPD pathogenesis compared to lipid and protein oxidative stress biomarkers.